Formaldehyde-free aqueous adhesive and preparation method thereof

By using environmentally friendly raw materials and modified epoxy resins and other technical means, formaldehyde-free water-based adhesives are prepared, which solves the problems of insufficient heat resistance and peel strength of traditional adhesives, and achieves higher performance and environmental protection.

CN119552620AInactive Publication Date: 2025-03-04SHANDONG SHUN INNOVATIVE MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411664666.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional adhesives contain harmful chemicals such as formaldehyde, which have insufficient heat resistance and peel strength, and may release volatile organic compounds, affecting the environment and human health.

Method used

Using environmentally friendly raw materials, a formaldehyde-free aqueous adhesive is prepared by combining bio-based polyether polyols, modified epoxy resins and specific crosslinking agents to improve its heat resistance and peel strength.

Benefits of technology

It significantly improves the heat resistance and peel strength of the adhesive, reduces the potential risks to the environment and human health, and is suitable for a wider range of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a formaldehyde-free water-based adhesive and a preparation method thereof, and belongs to the technical field of polymer adhesives, the adhesive adopts environment-friendly raw materials such as bio-based polyether polyol, modified epoxy resin and the like, and the water-based adhesive with excellent heat resistance and mechanical strength is prepared by finely regulating reaction conditions. Compared with the prior art, the adhesive does not contain harmful chemical substances, is friendly to the environment and human health, is suitable for high-temperature application fields such as aerospace, electronic and electrical appliances and the like, has a wide market prospect, is simple in preparation process and high in cost benefit, and is favorable for promoting industrial application of the environment-friendly adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer adhesives, and in particular to a formaldehyde-free water-based adhesive and a preparation method thereof. Background Art

[0002] In modern industry and daily life, adhesives are widely used in many fields such as construction, automobiles, electronics, packaging, and wood processing. However, the main disadvantages of traditional adhesives include containing chemicals that are harmful to the environment and human health, such as formaldehyde, which may cause indoor air pollution and health problems; poor heat resistance and chemical resistance, which limits their application in high temperature or harsh chemical environments; insufficient bonding strength and peel strength, which affects the durability and reliability of the bonding effect; slow drying speed, which affects production efficiency and construction time; and the possible release of volatile organic compounds (VOCs) during the curing process, which poses a threat to the environment and human health. These shortcomings have led to an increase in demand for environmentally friendly and high-performance adhesives, and promoted the research and development and application of new adhesives such as formaldehyde-free water-based adhesives. Therefore, the development of environmentally friendly adhesives has become an important direction for the industry.

[0003] Chinese invention patent CN115353840A discloses a water-based adhesive for cast-in-place runway and its preparation method, which belongs to the field of polymer adhesives. The water-based adhesive of the invention is composed of the following components: 1000-1200 parts of water, 45-70 parts of phosphate emulsifier, 10-30 parts of anionic non-ionic emulsifier, 10-15 parts of pH neutralizer, 0.5-2 parts of pH buffer, 2-7 parts of initiator, 0-100 parts of polyurethane containing polymerizable double bonds, 100-300 parts of n-butyl methacrylate, 400-650 parts of methyl methacrylate, 350-500 parts of isooctyl acrylate, 5-10 parts of hydroxyethyl methacrylate, 15-35 parts of methacrylic acid, 10-50 parts of cross-linking agent, 0.5-2 parts of oxidant, 0.5-2 parts of reducing agent, 0.05-0.5 parts of defoaming agent, and 1-3 parts of preservative. The water-based adhesive of the invention has good mechanical properties, does not contain APEO, and is non-toxic and harmless. However, the peel strength and heat resistance of the water-based adhesive prepared by the invention need to be improved. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention aims to provide a formaldehyde-free water-based adhesive and a preparation method thereof. The adhesive adopts environmentally friendly raw materials and does not contain harmful chemicals such as formaldehyde, thereby reducing potential risks to the environment and human health. At the same time, the adhesive of the present invention has better heat resistance and peel strength, and is suitable for a wider range of industrial applications.

[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0006] A method for preparing a formaldehyde-free water-based adhesive is as follows, in parts by weight:

[0007] First, 2-4 parts of polyol, 1-3 parts of dicyclohexylmethane-4,4'-diisocyanate and 0.5-0.7 parts of acetone are mixed and added into a reaction kettle. Under the condition of maintaining the temperature at 80-95°C, 0.05-0.2 parts of catalyst, 1-1.5 parts of modified epoxy resin and 0.15-0.2 parts of tartronic acid are added in sequence to ensure that the components are fully mixed. Subsequently, the mixed system is cooled to 35-45°C, and 0.1-0.3 parts of sodium diethyldithiocarbamate are added to obtain to the pretreated material; under the condition of 35-45°C, add 0.2-0.4 parts of N,N-diethylmethylamine to the pretreated material, and continue stirring for 0.5-2 hours, then add 0.05-0.1 parts of a cross-linking agent, and use 5-7 parts of water for emulsification treatment, which lasts for 40-60 minutes, during which time, add 0.05-0.2 parts of a defoaming agent, use a pH neutralizer to adjust the pH value of the mixture to 7-8, add 0.1-0.3 parts of a preservative, mix well, and obtain a formaldehyde-free water-based adhesive.

[0008] The polyol is selected from at least one of bio-based polyether polyol and polycaprolactone diol.

[0009] The catalyst is dibutyltin dilaurate.

[0010] The pH neutralizer is aqueous ammonia with a concentration of 24-26 wt%.

[0011] The preservative is MIT-10.

[0012] The defoamer is at least one of BYK-1740, BYK-022 and BYK-024.

[0013] The crosslinking agent is triethylenetetramine.

[0014] The preparation method of the modified epoxy resin is as follows, in parts by weight:

[0015] S1. Add 0.5-2 parts of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane and 8-12 parts of epoxy resin into a three-necked flask, raise the temperature to 130-145° C. and introduce nitrogen to exhaust the air, stir evenly, then add 0.005-0.01 parts of dibutyltin dilaurate, treat for 4-6 hours, and cool to room temperature to obtain a pre-modified resin;

[0016] S2, adding 0.5-2 parts of bisphenol A propylene glycol dimethacrylate and 1-3 parts of tris(glycidoxypropyldimethylsiloxy)phenylsilane to the pre-modified resin prepared in step S1, raising the temperature to 70-80°C while introducing nitrogen to exhaust the air, stirring evenly, then adding 0.001-0.003 parts of platinum catalyst, treating for 0.5-2 hours, to obtain a modified epoxy resin.

[0017] The functions of each substance in the present invention are as follows:

[0018] As one of the main components of adhesives, bio-based polyether polyols provide hydroxyl groups to react with isocyanates to form polyurethanes, thereby providing the basic bonding properties of the adhesive.

[0019] Dicyclohexylmethane-4,4'-diisocyanate, as the isocyanate component, reacts with polyols to form polyurethanes, enhancing the mechanical properties and chemical resistance of the adhesive.

[0020] The catalyst dibutyltin dilaurate accelerates the reaction between polyol and isocyanate and improves the reaction efficiency.

[0021] Modified epoxy resin improves the heat resistance, mechanical strength and chemical stability of the adhesive by introducing organic siloxane and specific functional groups.

[0022] Succinic acid may act as a pH adjuster or cross-linking agent, affecting the viscosity and curing characteristics of the adhesive.

[0023] Sodium diethyldithiocarbamate acts as an accelerator or stabilizer and may help improve the storage stability or reaction process of the adhesive.

[0024] Triethylenetetramine is used as a crosslinking agent to increase the crosslinking density of the adhesive and improve its mechanical properties.

[0025] Water is used as a medium in the emulsification process and affects the viscosity and coating performance of the adhesive.

[0026] Defoamers control and reduce foam in adhesives to ensure product quality.

[0027] pH neutralizers adjust the pH value of the adhesive, affecting the stability and curing process of the adhesive.

[0028] Preservatives prevent microbial degradation of adhesives during storage and use, extending their shelf life.

[0029] 2,4,6-Trivinyl-2,4,6-trimethylcyclotrisiloxane as part of the modified epoxy resin provides additional crosslinking points and heat resistance.

[0030] Bisphenol A propylene glycol dimethacrylate is used as a part of modified epoxy resin to increase the heat resistance and mechanical strength of the adhesive.

[0031] Tris(glycidoxypropyldimethylsiloxy)phenylsilane as part of modified epoxy resin enhances the chemical and heat resistance of adhesives.

[0032] The combination and interaction of these substances enable the formaldehyde-free water-based adhesive of the present invention to have excellent properties, including good heat resistance, peel strength and environmental adaptability.

[0033] Compared with the prior art, it has the following beneficial effects:

[0034] 1) The present invention introduces modified epoxy resin to enhance the crosslinking density and network stability of the adhesive, thereby significantly improving the heat resistance of the adhesive. This structural modification enables the adhesive to better maintain the integrity of the molecular structure in a high temperature environment and exhibit excellent thermal stability.

[0035] 2) Due to the introduction of the modified epoxy resin in the present invention, the adhesive of the present invention forms a denser cross-linked network during the curing process, thereby improving the cohesion and bonding strength of the adhesive. This structural optimization enables the adhesive to exhibit higher peel strength.

[0036] 3) The present invention uses bio-based polyether polyol as one of the main raw materials, and uses environmentally friendly catalysts and preservatives, which reduces the use of harmful chemicals, making the final product safer, harmless and environmentally friendly. This environmentally friendly formula design is in line with the current trend of green chemistry and sustainable development, and helps promote the development and application of environmentally friendly adhesives. DETAILED DESCRIPTION

[0037] Main sources of substances:

[0038] Bio-based polyether polyol: molecular weight 2000, CAS number: 345260-48-2, Guangdong Wengjiang Chemical Reagent Co., Ltd.

[0039] Defoaming agent BYK-1740 was purchased from BYK.

[0040] Preservative MIT-10, product model: MIT10, was purchased from Changzhou Xinnuoke Chemical Co., Ltd.

[0041] Epoxy resin, brand: E-44, Wuxi Qianguang Chemical Raw Materials Co., Ltd.

[0042] Platinum catalyst, item number: 68478-92-2, high activity 5000ppm, Wuhan Kemik Biopharmaceutical Technology Co., Ltd.

[0043] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.

[0044] The design idea of ​​the present invention is to prepare a formaldehyde-free water-based adhesive by combining multiple components such as bio-based polyether polyols, dicyclohexylmethane-4,4'-diisocyanate, and modified epoxy resin. The crosslinking density and thermal stability of the adhesive are enhanced by utilizing the properties of substances such as 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane and bisphenol A propylene glycol dimethacrylate, thereby improving its heat resistance and mechanical strength. At the same time, by finely controlling the proportion of each component and the reaction conditions, the performance of the adhesive is optimized to meet specific application requirements. In addition, environmentally friendly raw materials and catalysts are used to ensure that the product is safe, non-toxic and harmless, and to promote the development of environmentally friendly adhesives.

[0045] Example 1

[0046] A method for preparing a formaldehyde-free water-based adhesive is as follows, in parts by weight:

[0047] First, 3 kg of bio-based polyether polyol, 2 kg of dicyclohexylmethane-4,4'-diisocyanate and 0.6 kg of acetone were mixed and added into a reactor. Under the condition of maintaining the temperature at 90°C, 0.1 kg of dibutyltin dilaurate, 1.2 kg of modified epoxy resin and 0.18 kg of succinic acid were added in sequence to ensure that the components were fully mixed. Subsequently, the mixed system was cooled to 40°C, and 0.2 kg of sodium diethyldithiocarbamate was added to obtain a pretreated product. At 40°C, 0.3 kg of N,N-diethylmethylamine was added to the pretreated material and stirred for 1 hour, then 0.08 kg of triethylenetetramine was added, and 6 kg of water was used for emulsification for 50 minutes. During this process, 0.1 kg of defoamer BYK-1740 was added to control the foam, and 25 wt% ammonia water was used to adjust the pH value of the mixture to neutral, and 0.2 kg of preservative MIT-10 was added. After mixing evenly, a formaldehyde-free water-based adhesive was obtained.

[0048] The preparation method of the modified epoxy resin is as follows:

[0049] S1. Add 1 kg of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane and 10 kg of epoxy resin into a three-necked flask, raise the temperature to 140° C. and introduce nitrogen to exhaust the air, stir evenly, then add 0.008 kg of dibutyltin dilaurate, treat for 5 hours, and cool to room temperature to obtain a pre-modified resin;

[0050] S2. Add 1 kg of bisphenol A propylene glycol dimethacrylate and 2 kg of tris(glycidoxypropyldimethylsiloxy)phenylsilane to the pre-modified resin prepared in step S1, increase the temperature to 75°C and introduce nitrogen to exhaust the air, stir evenly, then add 0.002 kg of platinum catalyst, treat for 1 hour, and obtain a modified epoxy resin.

[0051] Example 2

[0052] The preparation method of a formaldehyde-free water-based adhesive is basically the same as that of Example 1, the only difference being that the preparation method of the modified epoxy resin is different.

[0053] The preparation method of the modified epoxy resin is as follows:

[0054] S1, add 1kg tri(vinyldimethylsiloxy)methylsilane and 10kg epoxy resin into a three-necked flask, raise the temperature to 140°C and introduce nitrogen to exhaust the air, stir evenly, then add 0.008kg dibutyltin dilaurate, treat for 5 hours, cool to room temperature, and obtain a pre-modified resin;

[0055] S2. Add 1 kg of bisphenol A propylene glycol dimethacrylate and 2 kg of tris(glycidoxypropyldimethylsiloxy)phenylsilane to the pre-modified resin prepared in step S1, increase the temperature to 75°C and introduce nitrogen to exhaust the air, stir evenly, then add 0.002 kg of platinum catalyst, treat for 1 hour, and obtain a modified epoxy resin.

[0056] Example 3

[0057] The preparation method of a formaldehyde-free water-based adhesive is basically the same as that of Example 1, the only difference being that the preparation method of the modified epoxy resin is different.

[0058] The preparation method of the modified epoxy resin is as follows:

[0059] S1. Add 1 kg of 1,3,5-trivinyl-1,1,3,5,5-pentamethyltrisilane and 10 kg of epoxy resin into a three-necked flask, raise the temperature to 140° C. and introduce nitrogen to exhaust the air, stir evenly, then add 0.008 kg of dibutyltin dilaurate, treat for 5 hours, and cool to room temperature to obtain a pre-modified resin;

[0060] S2. Add 1 kg of bisphenol A propylene glycol dimethacrylate and 2 kg of tris(glycidoxypropyldimethylsiloxy)phenylsilane to the pre-modified resin prepared in step S1, increase the temperature to 75°C and introduce nitrogen to exhaust the air, stir evenly, then add 0.002 kg of platinum catalyst, treat for 1 hour, and obtain a modified epoxy resin.

[0061] Example 4

[0062] The preparation method of a formaldehyde-free water-based adhesive is basically the same as that of Example 1, the only difference being that the preparation method of the modified epoxy resin is different.

[0063] The preparation method of the modified epoxy resin is as follows:

[0064] S1, add 1 kg of vinyl-terminated polyphenylsiloxane and 10 kg of epoxy resin into a three-necked flask, raise the temperature to 140° C. and introduce nitrogen to exhaust the air, stir evenly, then add 0.008 kg of dibutyltin dilaurate, treat for 5 hours, and cool to room temperature to obtain a pre-modified resin;

[0065] S2. Add 1 kg of bisphenol A propylene glycol dimethacrylate and 2 kg of tris(glycidoxypropyldimethylsiloxy)phenylsilane to the pre-modified resin prepared in step S1, increase the temperature to 75°C and introduce nitrogen to exhaust the air, stir evenly, then add 0.002 kg of platinum catalyst, treat for 1 hour, and obtain a modified epoxy resin.

[0066] Example 5

[0067] The preparation method of a formaldehyde-free water-based adhesive is basically the same as that of Example 1, the only difference being that the preparation method of the modified epoxy resin is different.

[0068] The preparation method of the modified epoxy resin is as follows:

[0069] S1. Add 1 kg of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane and 10 kg of epoxy resin into a three-necked flask, raise the temperature to 140° C. and introduce nitrogen to exhaust the air, stir evenly, then add 0.008 kg of dibutyltin dilaurate, treat for 5 hours, and cool to room temperature to obtain a pre-modified resin;

[0070] S2. Add 1 kg of 4,4'-methylenebis[2-allylphenol] and 2 kg of tris(glycidoxypropyldimethylsiloxy)phenylsilane to the pre-modified resin prepared in step S1, increase the temperature to 75°C and introduce nitrogen to exhaust the air, stir evenly, then add 0.002 kg of platinum catalyst, treat for 1 hour, and obtain a modified epoxy resin.

[0071] Example 6

[0072] The preparation method of a formaldehyde-free water-based adhesive is basically the same as that of Example 1, the only difference being that the preparation method of the modified epoxy resin is different.

[0073] The preparation method of the modified epoxy resin is as follows:

[0074] S1. Add 1 kg of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane and 10 kg of epoxy resin into a three-necked flask, raise the temperature to 140° C. and introduce nitrogen to exhaust the air, stir evenly, then add 0.008 kg of dibutyltin dilaurate, treat for 5 hours, and cool to room temperature to obtain a pre-modified resin;

[0075] S2. Add 1 kg of 2,2'-diallyl 4,4'-bisphenol and 2 kg of tri(glycidoxypropyldimethylsiloxy)phenylsilane to the pre-modified resin prepared in step S1, increase the temperature to 75°C and introduce nitrogen to exhaust the air, stir evenly, then add 0.002 kg of platinum catalyst, treat for 1 hour, and obtain a modified epoxy resin.

[0076] Comparative Example 1

[0077] The preparation method of a formaldehyde-free water-based adhesive is basically the same as that of Example 1, the only difference being that the preparation method of the modified epoxy resin is different.

[0078] The preparation method of the modified epoxy resin is as follows:

[0079] S1, add 1kg of vinylmethylbis(trimethylsiloxy)silane and 10kg of epoxy resin into a three-necked flask, raise the temperature to 140°C and introduce nitrogen to exhaust the air, stir evenly, then add 0.008kg of dibutyltin dilaurate, treat for 5 hours, and cool to room temperature to obtain a pre-modified resin;

[0080] S2. Add 1 kg of bisphenol A propylene glycol dimethacrylate and 2 kg of tris(glycidoxypropyldimethylsiloxy)phenylsilane to the pre-modified resin prepared in step S1, increase the temperature to 75°C and introduce nitrogen to exhaust the air, stir evenly, then add 0.002 kg of platinum catalyst, treat for 1 hour, and obtain a modified epoxy resin.

[0081] Comparative Example 2

[0082] The preparation method of a formaldehyde-free water-based adhesive is basically the same as that of Example 1, the only difference being that the preparation method of the modified epoxy resin is different.

[0083] The preparation method of the modified epoxy resin is as follows:

[0084] S1. Add 1 kg of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane and 10 kg of epoxy resin into a three-necked flask, raise the temperature to 140° C. and introduce nitrogen to exhaust the air, stir evenly, then add 0.008 kg of dibutyltin dilaurate, treat for 5 hours, and cool to room temperature to obtain a pre-modified resin;

[0085] S2. Add 1 kg of diallyl bisphenol A and 2 kg of tri(glycidoxypropyldimethylsiloxy)phenylsilane to the pre-modified resin prepared in step S1, raise the temperature to 75°C and introduce nitrogen to exhaust the air, stir evenly, then add 0.002 kg of platinum catalyst, treat for 1 hour, and obtain a modified epoxy resin.

[0086] Comparative Example 3

[0087] A method for preparing a formaldehyde-free water-based adhesive is as follows, in parts by weight:

[0088] First, 3 kg of bio-based polyether polyol, 2 kg of dicyclohexylmethane-4,4'-diisocyanate and 0.6 kg of acetone were mixed and added into a reactor. Under the condition of maintaining the temperature at 90 ° C, 0.1 kg of dibutyltin dilaurate, 1.2 kg of epoxy resin and 0.18 kg of succinic acid were added in sequence to ensure that the components were fully mixed. Subsequently, the mixed system was cooled to 40 ° C, and 0.2 kg of sodium diethyldithiocarbamate was added to obtain a pretreated product. At 40°C, 0.3 kg of N,N-diethylmethylamine was added to the pretreated material and stirred for 1 hour, then 0.08 kg of triethylenetetramine was added, and 6 kg of water was used for emulsification for 50 minutes. During this process, 0.1 kg of defoamer BYK-020 was added to control the foam, and 25 wt% ammonia water was used to adjust the pH value of the mixture to neutral, and 0.2 kg of preservative MIT-10 was added. After mixing evenly, a formaldehyde-free water-based adhesive was obtained.

[0089] Test Example 1

[0090] Heat resistance test

[0091] 20g of the formaldehyde-free water-based adhesive prepared in the examples and comparative examples was placed in a thermogravimetric analyzer, with a nitrogen atmosphere, a temperature rise range of 30-600°C, and a temperature rise rate of 5°C / min. The heating temperature at which the mass retention rate reached 90% was recorded. The test results are shown in Table 1.

[0092]

[0093] Test Example 2

[0094] Peel strength test

[0095] The formaldehyde-free water-based adhesives prepared in the examples and comparative examples were tested according to GB / T 2790-1995 “180° peel strength test method for adhesives - flexible material to rigid material”.

[0096] Apply adhesive to the entire width of the bonded test piece, the adhesive length is 150mm, the adhesive thickness is controlled at 0.2mm, and pressure is applied evenly on the entire bonding surface, and heat and cure at 60℃ for 12h. Bend the unbonded end of the electrode sheet 180°, clamp the steel plate on the fixed chuck, and clamp the electrode sheet on the other end, the separation rate of the chuck is 100mm / min, and the effective peeling distance is at least 125mm.

[0097] The test results are shown in Table 2.

[0098]

[0099] It can be seen from the data in Tables 1-2 that the heat resistance and peel strength of the formaldehyde-free water-based adhesive prepared in Example 1 are better than those in Examples 2-6 and Comparative Examples 1-3.

[0100] The 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane used in Example 1 can form more crosslinking points with epoxy resin due to its unique cyclic structure and more vinyl functional groups, which enhances the interaction between molecules, thereby improving the crosslinking density and the stability of the network. This structure not only provides better heat resistance, because it can better maintain the integrity of the molecular structure at high temperatures, but also enhances the cohesion and bonding strength of the adhesive, which is directly reflected in the higher peel strength. In contrast, the siloxanes used in other embodiments and comparative examples are less in number or structural differences in functional groups, and the crosslinked network formed is not as effective as 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane in heat resistance and bonding performance, resulting in relatively low heat resistance and peel strength.

[0101] Bisphenol A propylene glycol dimethacrylate shows more excellent heat resistance and peel strength in Example 1 of the present invention, which is mainly due to its unique molecular structure. The molecule contains two hydroxyl groups, which provide multiple reaction sites and can form more chemical crosslinks with epoxy resin, thereby enhancing the density and stability of the crosslinked network. In addition, the methyl and acrylate groups on its side chains help to improve the flexibility and bonding properties of the molecule, which helps to maintain the structural integrity of the adhesive under high temperature conditions, thereby showing better heat resistance and stability. At the same time, these characteristics also help to improve the bonding strength of the adhesive, especially in curing and peeling tests, which makes the adhesive of Example 1 superior to the adhesives in other embodiments and comparative examples in terms of heat resistance and peel strength.

[0102] The modified epoxy resin used in Example 1 introduces 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane and bisphenol A propylene glycol dimethacrylate, which not only enhance the crosslinking density of the epoxy resin, but also provide additional thermal stability and mechanical strength due to the introduction of siloxane. This structural modification significantly improves the heat resistance of the adhesive because it can better maintain its network structure at high temperatures. At the same time, these ingredients also help to improve the bonding strength and toughness of the adhesive, which is more obvious in the peel strength test. In contrast, the epoxy resin directly used in Comparative Example 3 lacks these enhanced properties and is therefore inferior to the modified epoxy resin in terms of heat resistance and peel strength.

Claims

1. A method for preparing a formaldehyde-free water-based adhesive, characterized in that: The method is as follows, in parts by weight: First, 2-4 parts of polyol, 1-3 parts of dicyclohexylmethane-4,4'-diisocyanate and 0.5-0.7 parts of acetone are mixed and added into a reaction kettle. Under the condition of maintaining the temperature at 80-95°C, 0.05-0.2 parts of catalyst, 1-1.5 parts of modified epoxy resin and 0.15-0.2 parts of tartronic acid are added in sequence to ensure that the components are fully mixed. Subsequently, the mixed system is cooled to 35-45°C, and 0.1-0.3 parts of sodium diethyldithiocarbamate are added to obtain to the pretreated material; under the condition of 35-45°C, add 0.2-0.4 parts of N,N-diethylmethylamine to the pretreated material, and continue stirring for 0.5-2 hours, then add 0.05-0.1 parts of a cross-linking agent, and use 5-7 parts of water for emulsification treatment, which lasts for 40-60 minutes, during which time, add 0.05-0.2 parts of a defoaming agent, use a pH neutralizer to adjust the pH value of the mixture to 7-8, add 0.1-0.3 parts of a preservative, mix well, and obtain a formaldehyde-free water-based adhesive.

2. The method for preparing the formaldehyde-free water-based adhesive according to claim 1, characterized in that: The polyol is selected from at least one of bio-based polyether polyol and polycaprolactone diol.

3. The method for preparing the formaldehyde-free water-based adhesive according to claim 1, characterized in that: The catalyst is dibutyltin dilaurate.

4. The method for preparing the formaldehyde-free water-based adhesive according to claim 1, characterized in that: The pH neutralizer is aqueous ammonia with a concentration of 24-26 wt%.

5. The method for preparing the formaldehyde-free water-based adhesive according to claim 1, characterized in that: The preservative is MIT-10.

6. The method for preparing the formaldehyde-free water-based adhesive according to claim 1, characterized in that: The defoamer is at least one of BYK-1740, BYK-022 and BYK-024.

7. The method for preparing the formaldehyde-free water-based adhesive according to claim 1, characterized in that: The cross-linking agent is triethylenetetramine.

8. The method for preparing the formaldehyde-free water-based adhesive according to claim 1, characterized in that: The preparation method of the modified epoxy resin is as follows, in parts by weight: S1. Add 0.5-2 parts of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane and 8-12 parts of epoxy resin into a three-necked flask, raise the temperature to 130-145° C. and introduce nitrogen to exhaust the air, stir evenly, then add 0.005-0.01 parts of dibutyltin dilaurate, treat for 4-6 hours, and cool to room temperature to obtain a pre-modified resin; S2, adding 0.5-2 parts of bisphenol A propylene glycol dimethacrylate and 1-3 parts of tris(glycidoxypropyldimethylsiloxy)phenylsilane to the pre-modified resin prepared in step S1, raising the temperature to 70-80°C while introducing nitrogen to exhaust the air, stirring evenly, then adding 0.001-0.003 parts of platinum catalyst, treating for 0.5-2 hours, to obtain a modified epoxy resin.

9. A formaldehyde-free water-based adhesive, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Water-based adhesive for cast-in-place runway and preparation method of water-based adhesive

    CN115353840A

  • Epoxy resin modified waterborne polyurethane adhesive for building and preparation method thereof

    CN109749690A